2003
DOI: 10.1248/bpb.26.233
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CAWS, a Mannoprotein-.BETA.-glucan Complex of Candida albicans, on Leukocyte, Endothelial Cell, and Platelet Functions in Vitro.

Abstract: Candida albicans is a medically important fungus which induces a disseminated candidasis and candidemia in immunocompromised hosts, and releases a polysaccharide fraction into the blood. We recently found that C. albicans released a water-soluble polysaccharide fraction (CAWS) into synthetic medium and demonstrated that CAWS was mainly composed of a complex of mannan and b b-glucan. In the murine system, CAWS showed a lethality resembling anaphylactic shock when administered i.v., and induced coronary arteriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 31 publications
0
32
0
1
Order By: Relevance
“…We first screened strains of mice for sensitivity to lethal toxicity (16,17). Examination of various strains revealed marked differences in sensitivity among the strains, with C3H exhibiting markedly high sensitivity and DBA/2 exhibiting markedly low sensitivity, and fatality could not be confirmed over the entire range of concentrations used.…”
Section: Caws Lethal Activity Organ Distribution and Elimination Ratmentioning
confidence: 99%
See 1 more Smart Citation
“…We first screened strains of mice for sensitivity to lethal toxicity (16,17). Examination of various strains revealed marked differences in sensitivity among the strains, with C3H exhibiting markedly high sensitivity and DBA/2 exhibiting markedly low sensitivity, and fatality could not be confirmed over the entire range of concentrations used.…”
Section: Caws Lethal Activity Organ Distribution and Elimination Ratmentioning
confidence: 99%
“…Therefore, the in vitro activity of CAWS was screened using several evaluation systems (17). As a result, it was found that at low concentrations of CAWS, a weak action that promotes the production of cytokines such as IL-6 and IFN-γ was observed in mouse spleen cells.…”
Section: Screening For Caws Activitymentioning
confidence: 99%
“…administration (12,13). As a positive control, a closed colony of ICR mice was used, in which ϳ100% acute lethal activity is observed.…”
Section: Acute Lethal Activity In Caws-administered Micementioning
confidence: 99%
“…CAWS was found to be composed of a mannoprotein-b-glucan complex, to be able to activate limulus G factor, 6) to demonstrate an activating effect on vascular endothelial cells, platelets, and lymphocytes, and to demonstrate vasculitis-inducing activity when administered to mice. [7][8][9][10][11] Moreover, CAWS caused an acute lethal reaction when administered intravenously to mice. The vasculitis was strongly related to the structure of the mannan moiety, and the activity was significantly reduced in the presence of a beta-1,2-linked mannosyl segment which was synthesized under specific conditions.…”
mentioning
confidence: 99%